A process for preparing activated carbon using coconut shell as raw material

The porous activated carbon prepared by coconut shell combines the modification treatment of chitosan and zirconium aluminum coupling agent to form a metal organic frame structure, solving the problem of low adsorption capacity of traditional adsorption materials and achieving low cost and efficient adsorption effect of organic dyes.

CN119098159BActive Publication Date: 2025-04-29广东韩研活性炭科技股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411490182.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-06-20
Filing Date
2024-10-24
Publication Date
2025-04-29
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

Traditional adsorption materials used to remove methylene blue in water have low adsorption capacity, high cost, complex preparation process, poor stability and low selectivity, which limits their practical application.

Method used

Coconut shells are used as raw material, and through composite treatment with chitosan, zirconium aluminum coupling agent and aminothiophenyl thiophenyl is formed, the porous structure activated carbon is formed, and the porogenic effect of chitosan and the modification effect of zirconium aluminum coupling agent is used to combine the organic modification of aminothiophenyl thiophenyl to form a metal organic framework structure to improve the adsorption capacity of activated carbon.

Benefits of technology

It significantly improves the adsorption capacity of activated carbon on organic dyes, reduces production costs and energy consumption, has a simple preparation process, and has significantly better adsorption effect than traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119098159B_ABST
    Figure CN119098159B_ABST
Patent Text Reader

Abstract

The present invention relates to a process for preparing activated carbon using coconut shell as raw material, and belongs to the technical field of activated carbon. A process for preparing activated carbon using coconut shell as raw material comprises the steps of: 1) washing, crushing, sieving and drying the coconut shell to obtain coconut shell particles; 2) stirring and mixing the coconut shell particles and chitosan solution, adding a modified solution, heating and stirring, filtering and taking solids, washing, drying and roasting to obtain prefabricated activated carbon; 3) placing the prefabricated activated carbon in a reactor, adding aminothiophenol, deionized water and hydrochloric acid, stirring and mixing, adding an initiator under an inert atmosphere, stirring and reacting, centrifuging and taking solids, washing, freeze-drying, and obtaining. The production process of the activated carbon prepared by the present invention has low cost and low energy consumption, and the finally prepared activated carbon significantly improves the adsorption capacity of organic dyes through the joint action of multiple adsorption mechanisms.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority to Chinese patent application No. CN202410796692.9 filed on June 20, 2024. Technical Field

[0002] The invention belongs to the technical field of activated carbon and relates to a process for preparing activated carbon by using coconut shell as raw material. Background Art

[0003] Activated carbon is a specially treated carbon. Organic raw materials (fruit shells, coal, wood, etc.) are heated in an airtight condition to reduce non-carbon components (this process is called carbonization), and then react with gas to erode the surface and produce a microporous structure (this process is called activation). Since the activation process is a microscopic process, that is, the surface erosion of a large number of molecular carbides is point erosion, so the surface of activated carbon has countless tiny pores.

[0004] Methylene blue (MB) is one of the common cationic dyes in water bodies. Due to its strong toxicity and great harm, it has received widespread attention in the wastewater treatment process. In order to remove MB from sewage, researchers have adopted methods such as adsorption, photocatalysis, and biodegradation. Among them, the adsorption method is favored by researchers because of its low cost, high efficiency, simple operation, and easy regeneration of adsorbents. The adsorption material is a key factor affecting the adsorption effect. Adsorption materials such as chitosan, graphene oxide, and activated carbon have been reported many times for the removal of MB. However, traditional adsorption materials have low adsorption capacity, high cost, complex preparation process, poor stability, and low selectivity, which limits its practical application. Summary of the invention

[0005] The purpose of the present invention is to provide a process for preparing activated carbon by using coconut shell as raw material, and the activated carbon production process has low cost and low energy consumption.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A process for preparing activated carbon using coconut shell as raw material, the process comprising the following steps:

[0008] 1) washing, crushing, sieving and drying the coconut shell to obtain coconut shell particles;

[0009] 2) After the coconut shell particles and the chitosan solution are stirred and mixed, the modified solution is added dropwise, heated and stirred, and the solid is filtered, washed, and dried to obtain prefabricated activated carbon;

[0010] 3) The prefabricated activated carbon is placed in a reaction kettle, aminothiophenol, deionized water and hydrochloric acid are added and stirred, and then an initiator is added under an inert atmosphere and stirred for reaction, and then the solid is centrifuged, washed, and freeze-dried to obtain the product.

[0011] As a preferred technical solution of the present invention, in step 1), the sieving is through a 10-20 mesh sieve; the drying is at a temperature of 105-115° C. for 12-15 hours.

[0012] As a preferred technical solution of the present invention, in step 2), the chitosan solution consists of chitosan and deionized water; the mass fraction of the chitosan solution is 0.08-0.10%.

[0013] As a preferred technical solution of the present invention, in step 2), the mass ratio of the coconut shell particles, chitosan solution and modified solution is 20-22:80-85:10-12.

[0014] As a preferred technical solution of the present invention, in step 2), the modified solution is prepared by mixing a zirconium aluminum coupling agent and anhydrous ethanol in a mass ratio of 1.0-1.3:3.

[0015] As a preferred technical solution of the present invention, in step 2), the heating and stirring is performed at a temperature of 65-75° C. and stirring for 6-8 hours; and the drying is performed at a temperature of 80-85° C. and drying to constant weight.

[0016] As a preferred technical solution of the present invention, in step 2), the calcination is performed at 500-520° C. for 3-4 hours.

[0017] As a preferred technical solution of the present invention, in step 3), the usage ratio of the prefabricated activated carbon, aminothiophenol, deionized water, hydrochloric acid and initiator is 6-7g:0.45-0.50mL:90-95mL:0.40-0.42mL:0.82g.

[0018] As a preferred technical solution of the present invention, in step 3), the aminothiophenol is m-aminothiophenol; and the initiator is ammonium persulfate.

[0019] As a preferred technical solution of the present invention, in step 3), the stirring and mixing is performed at a rotation speed of 300-350 r / min for 30-45 min; and the inert atmosphere is a nitrogen atmosphere.

[0020] Beneficial effects of the present invention:

[0021] The production process cost of the activated carbon prepared by the present invention is low and the energy consumption is small. The activated carbon finally prepared significantly improves the adsorption capacity of organic dyes through the joint action of multiple adsorption mechanisms. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the SEM image of the prefabricated activated carbon in step 2) of Example 4;

[0023] Figure 2 This is the SEM image of the final product of step 3) in Example 4. DETAILED DESCRIPTION

[0024] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.

[0025] Example 1

[0026] A process for preparing activated carbon using coconut shell as raw material comprises the following steps:

[0027] 1) washing, crushing, sieving and drying the coconut shell to obtain coconut shell particles;

[0028] In step 1), the sieving is through a 10-mesh sieve; the drying is at a temperature of 105° C. for 12 hours;

[0029] 2) After the coconut shell particles and the chitosan solution are stirred and mixed, the modified solution is added dropwise, heated and stirred, and the solid is filtered, washed, and dried to obtain prefabricated activated carbon;

[0030] In step 2), the chitosan solution is composed of chitosan and deionized water; the mass fraction of the chitosan solution is 0.08%;

[0031] In step 2), the mass ratio of the coconut shell particles, chitosan solution and modified solution is 20:80:10;

[0032] In step 2), the modified solution is prepared by mixing a zirconium-aluminum coupling agent and anhydrous ethanol in a mass ratio of 1.0:3;

[0033] In step 2), the heating and stirring is performed at 65° C. for 6 hours; the drying is performed at 80° C. to a constant weight;

[0034] In step 2), the calcination is performed at 500° C. for 3 h;

[0035] 3) placing the prefabricated activated carbon in a reaction kettle, adding aminothiophenol, deionized water and hydrochloric acid, stirring and mixing, adding an initiator under an inert atmosphere, stirring and reacting, centrifuging to obtain a solid, washing, and freeze-drying to obtain the product;

[0036] In step 3), the ratio of the prefabricated activated carbon, aminothiophenol, deionized water, hydrochloric acid and initiator is 6 g: 0.45 mL: 90 mL: 0.40 mL: 0.82 g;

[0037] In step 3), the aminothiophenol is m-aminothiophenol; the initiator is ammonium persulfate;

[0038] In step 3), the stirring and mixing is carried out at a speed of 300 r / min for 30 min; and the inert atmosphere is a nitrogen atmosphere.

[0039] Example 2

[0040] A process for preparing activated carbon using coconut shell as raw material comprises the following steps:

[0041] 1) washing, crushing, sieving and drying the coconut shell to obtain coconut shell particles;

[0042] In step 1), the sieving is through a 12-mesh sieve; the drying is at a temperature of 108° C. for 13 hours;

[0043] 2) After the coconut shell particles and the chitosan solution are stirred and mixed, the modified solution is added dropwise, heated and stirred, and the solid is filtered, washed, and dried to obtain prefabricated activated carbon;

[0044] In step 2), the chitosan solution is composed of chitosan and deionized water; the mass fraction of the chitosan solution is 0.085%;

[0045] In step 2), the mass ratio of the coconut shell particles, chitosan solution and modified solution is 20.5:81:10.5;

[0046] In step 2), the modified solution is prepared by mixing a zirconium-aluminum coupling agent and anhydrous ethanol in a mass ratio of 1.1:3;

[0047] In step 2), the heating and stirring is performed at 68° C. for 6.5 h; the drying is performed at 81° C. to a constant weight;

[0048] In step 2), the calcination is performed at 505° C. for 3.2 h;

[0049] 3) placing the prefabricated activated carbon in a reaction kettle, adding aminothiophenol, deionized water and hydrochloric acid, stirring and mixing, adding an initiator under an inert atmosphere, stirring and reacting, centrifuging to obtain a solid, washing, and freeze-drying to obtain the product;

[0050] In step 3), the ratio of the prefabricated activated carbon, aminothiophenol, deionized water, hydrochloric acid and initiator is 6.2 g: 0.46 mL: 91 mL: 0.405 mL: 0.82 g;

[0051] In step 3), the aminothiophenol is m-aminothiophenol; the initiator is ammonium persulfate;

[0052] In step 3), the stirring and mixing is carried out at a rotation speed of 312 r / min for 34 min; and the inert atmosphere is a nitrogen atmosphere.

[0053] Example 3

[0054] A process for preparing activated carbon using coconut shell as raw material comprises the following steps:

[0055] 1) washing, crushing, sieving and drying the coconut shell to obtain coconut shell particles;

[0056] In step 1), the sieving is through a 15-mesh sieve; the drying is at a temperature of 110° C. for 13.5 hours;

[0057] 2) After the coconut shell particles and the chitosan solution are stirred and mixed, the modified solution is added dropwise, heated and stirred, and the solid is filtered, washed, and dried to obtain prefabricated activated carbon;

[0058] In step 2), the chitosan solution is composed of chitosan and deionized water; the mass fraction of the chitosan solution is 0.09%;

[0059] In step 2), the mass ratio of the coconut shell particles, chitosan solution and modified solution is 21:82:11;

[0060] In step 2), the modified solution is prepared by mixing a zirconium-aluminum coupling agent and anhydrous ethanol in a mass ratio of 1.15:3;

[0061] In step 2), the heating and stirring is performed at 70° C. and stirring for 7 hours; the drying is performed at 82° C. and drying to constant weight;

[0062] In step 2), the calcination is performed at 510° C. for 3.5 h;

[0063] 3) placing the prefabricated activated carbon in a reaction kettle, adding aminothiophenol, deionized water and hydrochloric acid, stirring and mixing, adding an initiator under an inert atmosphere, stirring and reacting, centrifuging to obtain a solid, washing, and freeze-drying to obtain the product;

[0064] In step 3), the ratio of the prefabricated activated carbon, aminothiophenol, deionized water, hydrochloric acid and initiator is 6.5 g: 0.48 mL: 92 mL: 0.41 mL: 0.82 g;

[0065] In step 3), the aminothiophenol is m-aminothiophenol; the initiator is ammonium persulfate;

[0066] In step 3), the stirring and mixing is carried out at a rotation speed of 325 r / min for 38 min; and the inert atmosphere is a nitrogen atmosphere.

[0067] Example 4

[0068] A process for preparing activated carbon using coconut shell as raw material comprises the following steps:

[0069] 1) washing, crushing, sieving and drying the coconut shell to obtain coconut shell particles;

[0070] In step 1), the sieving is through an 18-mesh sieve; the drying is at a temperature of 112° C. for 14.2 hours;

[0071] 2) After the coconut shell particles and the chitosan solution are stirred and mixed, the modified solution is added dropwise, heated and stirred, and the solid is filtered, washed, and dried to obtain prefabricated activated carbon;

[0072] In step 2), the chitosan solution is composed of chitosan and deionized water; the mass fraction of the chitosan solution is 0.095%;

[0073] In step 2), the mass ratio of the coconut shell particles, chitosan solution and modified solution is 21.5:84:11.5;

[0074] In step 2), the modified solution is prepared by mixing a zirconium-aluminum coupling agent and anhydrous ethanol in a mass ratio of 1.23:3;

[0075] In step 2), the heating and stirring is performed at 72° C. for 7.5 h; the drying is performed at 84° C. to a constant weight;

[0076] In step 2), the calcination is performed at 515° C. for 3.8 h;

[0077] 3) placing the prefabricated activated carbon in a reaction kettle, adding aminothiophenol, deionized water and hydrochloric acid, stirring and mixing, adding an initiator under an inert atmosphere, stirring and reacting, centrifuging to obtain a solid, washing, and freeze-drying to obtain the product;

[0078] In step 3), the ratio of the prefabricated activated carbon, aminothiophenol, deionized water, hydrochloric acid and initiator is 6.8 g: 0.49 mL: 94 mL: 0.415 mL: 0.82 g;

[0079] In step 3), the aminothiophenol is m-aminothiophenol; the initiator is ammonium persulfate;

[0080] In step 3), the stirring and mixing is carried out at a rotation speed of 338 r / min for 41 min; and the inert atmosphere is a nitrogen atmosphere.

[0081] Example 5

[0082] A process for preparing activated carbon using coconut shell as raw material comprises the following steps:

[0083] 1) washing, crushing, sieving and drying the coconut shell to obtain coconut shell particles;

[0084] In step 1), the sieving is through a 20-mesh sieve; the drying is at a temperature of 115° C. for 15 hours;

[0085] 2) After the coconut shell particles and the chitosan solution are stirred and mixed, the modified solution is added dropwise, heated and stirred, and the solid is filtered, washed, and dried to obtain prefabricated activated carbon;

[0086] In step 2), the chitosan solution is composed of chitosan and deionized water; the mass fraction of the chitosan solution is 0.10%;

[0087] In step 2), the mass ratio of the coconut shell particles, chitosan solution and modified solution is 22:85:12;

[0088] In step 2), the modified solution is prepared by mixing a zirconium-aluminum coupling agent and anhydrous ethanol in a mass ratio of 1.3:3;

[0089] In step 2), the heating and stirring is performed at 75° C. for 8 hours; the drying is performed at 85° C. to a constant weight;

[0090] In step 2), the calcination is performed at 520° C. for 4 hours;

[0091] 3) placing the prefabricated activated carbon in a reaction kettle, adding aminothiophenol, deionized water and hydrochloric acid, stirring and mixing, adding an initiator under an inert atmosphere, stirring and reacting, centrifuging to obtain a solid, washing, and freeze-drying to obtain the product;

[0092] In step 3), the ratio of the prefabricated activated carbon, aminothiophenol, deionized water, hydrochloric acid and initiator is 7 g: 0.50 mL: 95 mL: 0.42 mL: 0.82 g;

[0093] In step 3), the aminothiophenol is m-aminothiophenol; the initiator is ammonium persulfate;

[0094] In step 3), the stirring and mixing is carried out at a speed of 350 r / min for 45 min; and the inert atmosphere is a nitrogen atmosphere.

[0095] Comparative Example 1

[0096] Compared with Example 4, the difference in Comparative Example 1 is that deionized water replaces the chitosan solution, and the other components, preparation steps and parameters are the same.

[0097] Comparative Example 2

[0098] Compared with Example 4, Comparative Example 2 is different in that aluminate coupling agent HYA1 is used instead of zirconium aluminum coupling agent, and the other components, preparation steps and parameters are the same.

[0099] Comparative Example 3

[0100] Compared with Example 4, the difference in Comparative Example 3 is that anhydrous ethanol replaces the zirconium aluminum coupling agent, and the other components, preparation steps and parameters are the same.

[0101] Comparative Example 4

[0102] Compared with Example 4, the difference of Comparative Example 4 is that step 3) is not performed, and the remaining components, preparation steps and parameters are the same.

[0103] Adsorption performance test

[0104] Weigh 0.02 g of activated carbon prepared in Examples 1-5 and Comparative Examples 1-4 respectively, add into 200 mL of 200 mg / L methylene blue, acid red 18 and Congo red test solution, and measure the organic matter concentration in the test solution after adsorption for 2 hours, and then obtain the adsorption capacity. The test results are shown in Table 1.

[0105] Table 1

[0106]

[0107] From the test results in Table 1, it can be seen that compared with the activated carbon prepared in Examples 1-5 of the present invention and the activated carbon prepared in Comparative Examples 1-4, the activated carbon prepared in Examples 1-5 of the present invention has significantly better adsorption effects on methylene blue, acid red 18 and Congo red than Comparative Examples 1-4. Comparative analysis shows that the scheme of the present invention forms a self-assembled structure by mixing coconut shell particles and chitosan. Chitosan increases the contact between the zirconium-aluminum coupling agent and the coconut shell particles through the action of hydrogen bonds and coordination bonds, and increases the grafting rate of the zirconium-aluminum coupling agent. In addition, chitosan can also be used as a porogen to increase the pore structure of the activated carbon generated by roasting coconut shell particles. During the roasting process, the surface of the activated carbon is covered with a composite layer of aluminum oxide / zirconium oxide, which increases the thermal stability of the activated carbon, avoids collapse due to excessive activation, and is beneficial to the formation of micropores in the activated carbon, significantly improving the adsorption effect of the activated carbon. Compared with the single aluminum oxide layer generated on the surface of the activated carbon, the composite of zirconium oxide and aluminum oxide can effectively reduce the agglomeration phenomenon between aluminum oxide particles, so that aluminum oxide / zirconium oxide is on the surface of the activated carbon. The activated carbon is uniformly generated, and the pore structure of the alumina / zirconia layer can further increase the adsorption capacity of the activated carbon. Then, the prefabricated activated carbon is organically modified through the self-polymerization of aminothiophenol to form a metal-organic framework adsorption material. The metal composite layer on the surface of the activated carbon interacts with aminothiophenol, which can generate more polyaminothiophenol on the activated carbon, so that a large number of benzene ring structures, amino groups and thiol groups are introduced into the activated carbon. The amino group can be used as a hydrogen bond donor to form hydrogen bonds with nitrogen atoms in organic dyes. The hydrophobic structure of the benzene ring can form a π-π stacking effect with the aromatic ring of the dye. The pore structure of the activated carbon and the composite layer is combined to work together with multiple adsorption mechanisms to significantly improve the adsorption capacity of organic dyes.

[0108] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A process for preparing activated carbon using coconut shell as raw material, characterized in that: The process comprises the following steps: 1) Washing, crushing, sieving and drying the coconut shell to obtain coconut shell particles; 2) After the coconut shell particles and chitosan solution are stirred and mixed, the modified solution is added dropwise, heated and stirred, the solid matter is filtered out, washed, dried and then roasted to obtain prefabricated activated carbon; the mass ratio of the coconut shell particles, chitosan solution and modified solution is 20-22:80-85:10-12; the modified solution is prepared by mixing zirconium aluminum coupling agent and anhydrous ethanol in a mass ratio of 1.0-1.3:3; 3) placing the prefabricated activated carbon in a reaction kettle, adding aminothiophenol, deionized water and hydrochloric acid, stirring and mixing, adding an initiator under an inert atmosphere, stirring and reacting, centrifuging to obtain a solid, washing, and freeze-drying to obtain the prefabricated activated carbon; the dosage ratio of the prefabricated activated carbon, aminothiophenol, deionized water, hydrochloric acid and initiator is 6-7g: 0.45-0.50mL: 90-95mL: 0.40-0.42mL: 0.82g; In step 2), the heating and stirring is performed at 65-75°C for 6-8h; the drying is performed at 80-85°C to constant weight; In step 2), the calcination is performed at 500-520° C. for 3-4 hours; In step 2), the mass fraction of chitosan in the chitosan solution is 0.08-0.10%.

2. A process for preparing activated carbon using coconut shell as raw material according to claim 1, characterized in that: In step 1), the sieving is through a 10-20 mesh sieve; and the drying is at a temperature of 105-115° C. for 12-15 hours.

3. A process for preparing activated carbon using coconut shell as raw material according to claim 1, characterized in that: In step 2), the chitosan solution consists of chitosan and deionized water.

4. A process for preparing activated carbon using coconut shell as raw material according to claim 1, characterized in that: In step 3), the aminothiophenol is m-aminothiophenol; and the initiator is ammonium persulfate.

5. A process for preparing activated carbon using coconut shell as raw material according to claim 1, characterized in that: In step 3), the stirring and mixing is carried out at a speed of 300-350 r / min for 30-45 min; and the inert atmosphere is a nitrogen atmosphere.

Citation Information

Patent Citations

  • Preparation method of nano composite material capable of efficiently and selectively adsorbing mercury ions

    CN109261139A

  • Process for preparing activated carbon by taking coconut shells as raw materials

    CN115974079A